When the Law Fails to Protect Children with Disabilities from Sexual Abuse - Pidesta, Nigel Jordan Giorgia Nandito; Ayu, Hanuring; Zakariya, Hafid (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
Sexual abuse of children with disabilities represents a particularly complex form of sexual violence and poses significant challenges to the criminal justice system in Indonesia. This study aims to analyze the differences in the application of criminal law to perpetrators of child molestation against children with disabilities and those without, to assess the extent to which national legal frameworks have incorporated the principle of substantive justice for victims with disabilities, and to identify the key factors contributing to weak legal protection—both in terms of legal substance, institutional structure, and socio-cultural context. The study employs a normative legal approach, utilizing doctrinal analysis of statutory regulations alongside selected case studies. The findings reveal that, despite the existence of relevant legal instruments—such as Law No. 35 of 2014 on Child Protection, Law No. 8 of 2016 on Persons with Disabilities, and Law No. 12 of 2022 on Sexual Violence—legal protections for children with disabilities remain largely formalistic and fail to adequately address the specific needs of these vulnerable victims. The study concludes by emphasizing the urgent need for a fair and substantive reformulation of laws and policies, as well as a comprehensive restructuring of the criminal justice system to make it more responsive and inclusive toward vulnerable populations.